Design and mechanical properties of supramolecular polymeric materials based on host–guest interactions: the relation between relaxation time and fracture energy. Issue 42 (12th October 2020) - Konishi, Subaru; Kashiwagi, Yu; Watanabe, Go; Osaki, Motofumi; Katashima, Takuya; Urakawa, Osamu; Inoue, Tadashi; Yamaguchi, Hiroyasu; Harada, Akira; Takashima, Yoshinori
Abstract : The viscoelastic behaviour of the reversible cross-linking points, which could be tuned by the relaxation time and the tensile rate, improved the fracture energy of the supramolecular hydrogels. Abstract : Functional polymeric materials based on reversible noncovalent bonds have attracted much attention due to their mechanical and responsive properties. In particular, the association/dissociation of the reversible bond is widely known to improve the fracture energy of polymeric materials. Herein, we aimed to establish a general strategy for designing tough materials and investigated the relation between the lifetime of reversible bonds and the toughness of the material. We experimentally demonstrated the fracture energy in relation to the viscoelastic relaxation time ( τ ) of the reversible bonds and the observation time scale. We prepared supramolecular hydrogels cross-linked by inclusion complexes between α-cyclodextrin (αCD) and alkyl chains modified with cation units. τ varied widely in response to the kinetics of the threading/dethreading of the αCD unit. The viscoelastic behaviour of the reversible cross-linking points, which could be tuned by τ and the tensile rate, improved the fracture energy of the supramolecular hydrogels.